An examination of the Mobisam project and Grocott's Mail : towards mobile social accountability monitoring in Grahamstown - Reinecke, Romi Kami (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2015)
This thesis critically examines the nature and purpose of the MobiSAM partnership, in relation to its value as a model resonating with normative theories on the role of the media in South African democratic society. The MobiSAM project introduces a mobile polling application, designed for citizens to provide real-time, user-generated data on crucial municipal service delivery such as clean water in Grahamstown, Eastern Cape, South Africa. The project has partnered with the local community newspaper, Grocott's Mail, to broadcast this data, with the aim to facilitate citizen participation in public problem solving and support local government accountability in service delivery. Despite pervasive poverty in areas such as the Eastern Cape, mobile penetration in South Africa is near universal. The MobiSAM partnership is an ongoing effort to forge new links between social accountability monitors, new media, traditional media, citizens and local government around public issues in Grahamstown, in line with the development objectives of the post-apartheid South African state. The overall theoretical framework for this thesis is taken from Christians, Glasser, McQuail, Nordenstreng and White's Normative Theories of the Media, which provides an analysis of four roles of the media in a democratic society, that is: the monitorial, the facilitative, the radical and the collaborative roles. Within each of these roles, the stated journalistic approach is explored, that is investigative journalism, public journalism, radical journalism and development journalism. Public journalism is focused on as having the most resonance with the goals of the MobiSAM partnership. The chosen research design is a critical realist case study with the selected methods of thematic document analysis and, primarily, in-depth interviews with key project participants. The research goals were to analyse this primary data against the normative theory on the role of the media in a democratic society, and the 'real world' constraints posed by the project's specific political and socioeconomic context. The findings conclude by offering certain recommendations and areas for further research, such as the central importance of a dedicated municipal reporter for covering complex public issues. This critical realist case study, drawing on qualitative interviews with both the accountability monitors and the media practitioners, interrogates the philosophical understandings on the role of the media in this new project, towards an empirical model for advancing substantive socio-economic change through media in South Africa.
Keywords: Grocott's Mail (Grahamstown, -- South Africa); Electronic discussion groups -- South Africa -- Grahamstown; Citizen journalism -- South Africa -- Grahamstown; Municipal services -- South Africa -- Grahamstown; Government accountability -- South Africa -- Grahamstown; Social action -- South Africa -- Grahamstown; Municipal services -- Citizen participation; Municipal government -- South Africa -- Grahamstown